2011
DOI: 10.1016/j.jcrs.2011.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Holladay 2 intraocular lens formula for pediatric eyes in the absence of preoperative refraction

Abstract: The Holladay 2 formula had the least prediction error and absolute prediction error even in the absence of preoperative refraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 12 publications
1
24
0
1
Order By: Relevance
“…One study 11 has reported that age, AL, and K values did not influence predictive accuracy, except for the Holladay and Hoffer Q formulae that were influenced by AL. On the other hand, several authors 5,10,12 reported that a shorter AL had a significant bearing on the predictive accuracy of the IOL calculation formula.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One study 11 has reported that age, AL, and K values did not influence predictive accuracy, except for the Holladay and Hoffer Q formulae that were influenced by AL. On the other hand, several authors 5,10,12 reported that a shorter AL had a significant bearing on the predictive accuracy of the IOL calculation formula.…”
Section: Discussionmentioning
confidence: 99%
“…In adult eyes, it is known that even with state-of-the-art techniques and equipment, a surgeon who fails to optimize his constants could have less accurate outcomes than someone using older equipment who does optimize. 22 Trivedi et al 10 (Poster presentation at the annual meeting of the American Academy of Ophthalmology, 2011) reported that personalizing the lens constant improves the PE and APE in pediatric eyes. Whereas we found that the mean PE improved significantly after personalizing the lens constants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations